2011
DOI: 10.1111/j.1600-0838.2011.01412.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of strength development with resistance training and combined exercise training in type 2 diabetes

Abstract: Resistance training has been shown to increase strength in type 2 diabetes; however, it is unclear if combining resistance and aerobic training (A + R) impedes strength development compared with resistance training only (R). The purpose of this study was to compare changes in strength with A + R vs R in individuals with type 2 diabetes. We evaluated monthly workload increments in participants from the Diabetes Aerobic and Resistance Exercise clinical trial. Muscular strength was assessed through training volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 32 publications
0
16
0
3
Order By: Relevance
“…Furthermore, resistance training was done at one set of 15 repetitions in weeks 1-2. Then intensity of resistance training was increased from 2-3 sets of 12 to 10 repetitions in the weeks 3-10 (Table 1) [28]. All resistance trainings exercises were performed on machine-based resistance training equipment and included major muscles such as bilateral triceps pushing down, bilateral biceps curling, bending over the lateral pull down, bench pressing, leg pressing.…”
Section: Combined Exercise Training (Aerobic Training Plus Resistancementioning
confidence: 99%
“…Furthermore, resistance training was done at one set of 15 repetitions in weeks 1-2. Then intensity of resistance training was increased from 2-3 sets of 12 to 10 repetitions in the weeks 3-10 (Table 1) [28]. All resistance trainings exercises were performed on machine-based resistance training equipment and included major muscles such as bilateral triceps pushing down, bilateral biceps curling, bending over the lateral pull down, bench pressing, leg pressing.…”
Section: Combined Exercise Training (Aerobic Training Plus Resistancementioning
confidence: 99%
“…In the reviewed studies, different manners of performing the order of resistance and aerobic trainings were applied. Of these, six studies [13] [25] performed AT before RT in the same training sessions; three studies [12] [17] [21] conducted both training modalities in the same session, in circuit; one study [15] performed AT and RT in separate days; one study [24] used one weekly session for AT, one weekly session for RT and two weekly sessions with both training types, without specifying the order; one study [23] allowed the participants to choose the training order; whereas the other studies [18] [20] did not report the training order. Of the four studies that showed the best results in the glycaemic control, three of them performed AT before RT in the same sessions [14] [19] [25] and one of them allowed the participants to choose the order [23].…”
Section: Order Of the Modalitiesmentioning
confidence: 99%
“…In the present review, three studies compared CT with AT[13] [17][19], one study compared CT with RT[23], and five studies compared CT with both aerobic and resistance trainings separately performed[16] [18] [21] [24][25]. Of these, only one study did not find significant results in HbA1c levels in both aerobic and resistance trainings[13].In the intervention conducted by Lambers et al[17], comparing AT and CT groups, only CT found HbA1c reductions, whereas the other studies[16] [18] [19] [21] [24] [25] found greater reductions in HbA1c levels with CT in compar-…”
mentioning
confidence: 99%
“…Tradicionalmente, o LL tem sido identificado em diferentes tipos de exercícios, especialmente de características cíclicas 5 , e mais recentemente no exercício resistido (ER), com grande validade ecológica, por ser amplamente empregado na avaliação e prescrição do exercício no treinamento atlético e na reabilitação física 6 , visando benefícios cardiovasculares 7 , neuromusculares 8 e metabólicos 9 . No entanto, sua prescrição utiliza-se basicamente de métodos tradicionais para avaliação e acompanhamento da evolução no treinamento físico.…”
Section: Resumen Introducción: El Umbral Anaeróbico Se Identifica Comunclassified